Hercules prince of power ebook - Layton, Bob (Hercules: Prince Of Power (1982-1984)., 2018)
Collects Hercules: Prince Of Power (1982) #1-4 and Hercules: Prince Of Power (1984) #1-4. In space, no one can hear you shout ""Have at thee!""...unless you've got lungs like the Prince of Power! Centuries in the future, Hercules embarks on an extraterrestrial odyssey and finds there are more gods in the heavens than he imagined! With his computerized comrade the Recorder, he wows worshippers, attacks avatars and sires a son who may be an even more dangerous demigod than he is! Rigellians, Skrulls, carnivorous horses and more!